Geographic distribution, source analysis, and ecological risk assessment of PTEs in the topsoil of different land uses around the antimony tailings tank: A case study of Longwangchi tailings pond, Hunan, China. (June 2023) - Zou, Hao; Ren, Bozhi; Deng, Xinping; Li, Tongshen
Highlights: For the first time, the surface soil pollution of different land use types around antimony tailings pond in the "world antimony capital" area was investigated. The study area is highly polluted by Sb. Sb is the main element causing high ecological risk. Filled the gap in the study of the surrounding environment of antimony tailings pond. Abstract: Few studies have addressed the contamination of surface soils around antimony tailings ponds, and studying the contamination levels and sources of potentially toxic elements (PTEs) in soils around antimony tailings ponds and assessing the associated environmental risks are key steps in conducting environmental protection. Therefore, this study is the first to investigate the current status, spatial distribution, potential sources and ecological risks of Pb, Sb, Cr, Zn, Cd, As and Cu contamination in surface soils in woodlands, grasslands, farmlands and construction areas around the Longwangchi antimony tailings pond in Hunan, China. According to the analytic results of soil samples, the order of PTEs in terms of average concentration is: Sb > Zn > Cu > Pb > As > Cr > Cd. The cumulative index of land was applied to define Sb and Cd as extremely heavy pollution, and PLI divides the overall pollution level of soil into serious pollution levels. The ecological risk index was used to evaluate the risk characteristics of PTEs. The results showed that the ecological risk of Sb was particularly prominent, and 95% of the study area had reached a very high risk level. A quantitative comparison of ecological risk levels between different land uses revealed that there was a clear dividing line between regions, with built-up areas contributing the most to higher ecological risk at 8.89%, followed by 1.72% for grassland, 1.15% for agricultural land, and 0.57% for woodland. The visualization results of spatial distribution of PTEs exhibited that severe pollution occurred in the middle, north and southeast of the study area, and these distribution characteristics are mainly dictated by the polluted runoffs from tailings ponds and human activities. Principal component analysis (PCA) and positive matrix decomposition (PMF) were employed to identify the exact pollution sources, and the closer the determination coefficient (R 2 ) of PMF was to 1, the finer the pollution sources analyzed. A total of six potential sources of PTEs were analyzed by PMF: 36% of tailings pond contamination and mining operations, 8% atmospheric deposition, 19% traffic emissions, 9% combustion emissions, 11% natural sources, and 17% inputs related to agricultural production. This study is a complement to the study of environmental pollution around antimony tailing ponds, providing evaluation criteria for the pollution identification indicators of antimony tailing ponds.